Gap analysis in classroom assessment - Lomboy, Jhoanne Abenoja (Saint Louis College, City of San Fernando, La Union : [s.n.], 2018)
This phenomenological research explored the classroom assessment practices of teachers in the intermediate grade in Burgos District, Schools Division of La Union. A gap analysis was conducted between the global standards in assessment and existing assessment practices, the result served as basis for crafting the training program. Using a validated guide, a one-on-one semistructured interview was conducted among the participants, chosen purposively. After performing thematic analysis, it found that subscribe to the process: planning, administering, evaluating, analyzing, interpreting, reflecting, giving intervention and communicating.It also found that there are gaps exist between the actual classroom assessment practices from that of the global standards. It recommended, among others, that training program for the intermediate grade teachers should be adopted.
Bibliography: pages 77-80.
CHED-La Union
Keywords: Classroom management